Pope John Paul II, the Saints, and Communist Poland: The Papal Pilgrimages of 1979 and 1983 - Felak, James Ramon (The catholic historical review, 2014)
In his efforts to challenge Poland’s communist regime and shape the thinking of his countrymen on a variety of spiritual, moral, and political issues, Pope John Paul II made generous use of the saints. This article examines Ss. Wojciech, Stanisław, Hedwig, and Maximilian Kolbe, who figured prominently in John Paul’s addresses to Poles during his dramatic visits to his homeland in June 1979 and June 1983, and the ways in which he employed them on behalf of his campaign to encourage, instruct, and succor his fellow Poles.